Libras interpretation and mediation: a post-graduate case study (Research, Society and Development, 2021)
COVID-19 forced teachers to make use of Digital Information and Communication Technologies to promote learning in a virtual way. This article is a case study on the complexity between interpreting classes and mediating the learning, in the remote teaching model, of a deaf, who uses sign language student enrolled in the doctoral course. The mediation process through translation and interpretation required a whole different dynamic during synchronous and asynchronous classes. The data left lessons such as: the need for specific strategies for the teaching of deaf people, adequate equipment, a TILS performance that also mediates the learning and continuing training of professionals.